Archival Discipline in Dewey Decimal Classification - Manzoni, Laura; Vivan, Barbara; Botti, Isabella; Tori, Luisa; Pisani, Francesca (JLIS.it, 2017)
This paper regards the ways archival discipline is treated in DDC. After a short introduction about the discipline in Italy, the essay focuses on the analysis of division 020 of DDC 23, with specific attention to section 025 and with punctual reference to section 651, concerning archival material. The aim of the paper is to point out archival discipline’s peculiarities and its differences from library science, as well as underlining the critical issues on how this discipline is handled in DDC.